Legalisasi Bentuk Kelompok Usaha Untuk Peningkatan Produksi Olahan Bambu di Dusun Koloh Brora Desa Menggala Kabupaten Lombok Utara - Suryawati, Baiq Nurul; Wardani, Laila; Muttaqillah, Muttaqillah (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this service is to help business owners choose the right form of business, besides that, with the existence of business legalization, it can support home businesses to develop themselves and survive in business situations that are full of uncertainty. The method of implementing community service is carried out by providing assistance where information is provided regarding business legalization and the requirements that need to be prepared to obtain legalization, besides watching watching together is carried out as part of learning by looking at examples of other successful businesses. The community service participants are all young people who are included in the bamboo craftsmen group in Koloh Berora Hamlet. The business legalization chosen by the business owner is CV, the business legalization arrangement is carried out in the City of Mataram, because the bureaucracy in North Lombok has not been able to properly facilitate the legalization of the business. The craftsmen group put up signs as an effort to market their products, in line with the directions that have been given.